The Speed of Money Circulation and Inflation in Years 2005-2021 in Poland - Zbigniew STANIEK (Communications of International Proceedings, 2021)
Problems connected with inflation and unemployment constitute a significant issue, both in theory of economics, as well as in economic practice. There is also a continuous discussion concerning the value of money and factors influencing this value. Basic factors which should be taken into consideration at this point are the real GDP (with all objections concerning this economic measure) and inflation/deflation phenomena. The speed of money circulation also has a great impact. Its increasement accompanies inflation, even though there are no unambiguous cause and effect correlations. The speed of monetary units’ circulation increase may, however, be of an autonomic character, resulting from institutional conditions, and may foster inflation. These issues are strictly connected with complex relations of real and nominal spheres of economy, as well as specifying the role of money in economy (money is not solely a unit of account). The aim of this research was an attempt to capture relations between the speed of money circulation and phenomena of inflation. Differentiation of economic conditions in Poland, as well as economic changes in worlds’ economy were considered in the studied period. Crises in a global scale, especially financial crisis and crisis connected with COVID-19 pandemics were also of great significance.
Keywords: Quantity Theory of Money; Monetary Aggregates; Inflation; Speed of Money Circulation.